Attachment relationships and physical activity in adolescents: The mediation role of physical self-concept. (January 2016) - Li, Ru; Bunke, Sofia; Psouni, Elia
Abstract: Objectives: Based on the integration of attachment and physical self-perception perspectives, the present study examined links between adolescents' engagement in physical activity and their attachment relationships with mothers, fathers, and friends, respectively, and assessed the potential mediation role of physical self-perception in this link. Design and methods: Using a cross-sectional design, questionnaire data was obtained from 767 adolescents (49% boys, M age  = 12.92, SD = .86) and structural equation modeling was used to examine relationships among variables. Results: Attachment security with parents and friend was associated with higher levels of physical activity. There was partial support of the mediation role of physical self-perception, as adolescents who were securely attached to mother and friend perceived themselves as having better physical condition, which in turn predicted greater engagement in physical activity. The mediation role of physical self-perception between mother attachment and PA was stronger for female adolescents. Secure attachment to father had a direct positive effect on physical activity. The direct effect was strongest for male adolescents. Conclusions: Our findings highlight the importance of relationship-based intervention strategies to enhance and maintain healthy regular physical activity among adolescents. Highlights: Attachment security (mother/friend) predicted PA via physical self-perception. Attachment security (father) was directly related to youths' PA. The mediation effect of physical self-perception was stronger for girls. The direct effect of father attachment security on PA was stronger for boys. Physical conditioning was the only mediator between attachment and PA.